PENGELUARAN PEMELIHARAAN ASET TETAP PT PUPUK KALIMANTAN TIMUR DIVISI JASA PELAYANAN PABRIK DI KOTA BONTANG - Hasanah Susanti; Irwansyah Irwansyah; Musviyanti R (Faculty of Economics and Business Mulawarman University, 2015)
Formulation of the problem in this riset is how the suitability of recognition, presentation and disclosure of accounting zakat, infak and sedekah at BAZNAS in Bontang with the statement of financial accounting standard number 109 in 2011. In accordance with the above formulation of the problem, then the purpose of this riset is to analyze the recognition, presentation and disclosure of accounting zakat, infak and sedekah that of the BAZNAS in Bontang and identify compliance with the statement of financial accounting standard number 109 in 2011. The analytical tool used in this study is of SFAS number 109 in 2011. This analysis is done with 2 stages, making receipt journal and distribution of zakat, infak and sedekah, and then make financial statements in the fund statement, cash flow statement and statement of financial position. The results showed that BAZNAS in Bontang didn’t make recognition for the transaction in 2013, do not include the (express) a written statement of the percentage of the distribution funds amil and funds nonamil and reason on zakat, infak and sedekah in the annual report and not presenting the financial statements in the form of statement of changes in funds. Cash flow statement and balance sheet (statement of financial position). Thus it is known that the recognition, presentation and disclosure of accounting zakat, infak and sedekah BAZNAS Bontang not in accordance with SFAS number 109 in 2011. Keywords: accounting zakat, infak and sedekah, SFAS